Perancangan Wifi cerdas untuk destinasi wisata yang terintegrasi di wisata cerdas - Ruci Meiyanti; Muhammad Yusuf Bagus Rasyiidin; Fachroni Arbi Murad; Riri Fajriah (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2022)
The use of public wireless networks and not integrated between tourist destinations is an obstacle for visitors when moving to other tourist destinations. This is an obstacle to internet access in the tourism era 4.0. To overcome this, smart wifi is needed. Smart wifi is an integrated internet network access among other tourist destinations so as to expand the connectivity and interaction of tourist visitors. This study used the NDLC method. The result of this research was the design of smart wifi which was built on a wireless network with captive portal technology and barcode scanning. Smart wifi contributes to the development of digitalization in smart tourism, making it easier for visitors to get internet access in various tourist destinations.